Imperial-royal Czech Prose 2021. Over the books by Pavla Horáková The Heart of Europe and Jaroslav Rudiš Winterberg's Last Journey - Šidáková Fialová, Alena (Bohemica Olomucensia, 2023)
The study compares two novels: Rudiš's Winterberg's Last Journey and Horáková's The Heart of Europe. Both novels have a similar theme, namely the history of the Habsburg Empire, and are set in two time periods, but the narrator's conception and narrative style is different each time, as is the artistic achievement and the reader's conception.
Keywords: contemporary prose; fact-based novel; Habsburg Monarchy; Vienna Czechs; 19th and 20th century history